2002
DOI: 10.1207/s15328023top2901_08
|View full text |Cite
|
Sign up to set email alerts
|

Biography and Role Playing: Fostering Empathy in Abnormal Psychology

Abstract: In this article I describe a method of fostering empathy in undergraduate and graduate students of abnormal psychology. Students depicted a psychological disorder by writing a brief biography and then role playing the characters they developed. Students demonstrated understanding of the disorders by acting and interacting in a manner consistent with their character and diagnosing other student “characters” using criteria from the Diagnostic and Statistical Manual of Mental Disorders–IV (American Psychiatric As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 24 publications
2
53
0
3
Order By: Relevance
“…In related work, researchers explore the implications for empathic development beyond role-playing exercises (Goldstein & Winner, 2012;Poorman, 2002). According to Goldstein and Winner, "Role-playing beyond early childhood may be a route by which humans come to develop enhanced empathy and gain greater insight into others' beliefs and emotions."…”
Section: Resultsmentioning
confidence: 99%
“…In related work, researchers explore the implications for empathic development beyond role-playing exercises (Goldstein & Winner, 2012;Poorman, 2002). According to Goldstein and Winner, "Role-playing beyond early childhood may be a route by which humans come to develop enhanced empathy and gain greater insight into others' beliefs and emotions."…”
Section: Resultsmentioning
confidence: 99%
“…Fogg (2001) reported that learning through play raises learner interest in the topic. According to Poorman (2002), "integrating experiential learning activities in the classroom increased interest in the subject matter and understanding of course content" (p. 32). Learning through play provides the learners with the opportunity to construct knowledge in an interactive and participatory manner.…”
Section: Role-playing As a Teaching Strategymentioning
confidence: 99%
“…[6]Introductory Drilling: as the construction of scenario is finished, some of the students are being choosen or voluntarily propose himself to take the role based on the set scenario. After that, each student will start to drill themselves under the lecturer supervisions and guidance.…”
Section: O1 X O2mentioning
confidence: 99%
“…In a student centred model, students are guided to actively build their own scientific ideas to build their cognitive competence. [6] mentioned that according to the recent research finding, a role play strategy can enhance student interest to a subject and materials. So then it can also positively influence students understanding upon the concepts.…”
Section: Introductionmentioning
confidence: 99%